Estimating optimal resource allocation in the inpatient department using simulation and data envelopment analysis - Nur Fatini Binti Rasidi,; Nazhatul Sahima Mohd Yusoff,; Adibah Shuib,; Abd Yazid Md Noh,; Norfarziah Adna, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The inpatient department is one of the important departments at Universiti Sains Malaysia Hospital (HUSM) which ensures that the patients will get their first checkup by the nurse within 15 minutes after getting bed. The inpatient department encounters problems as it wrestles with the long waiting time for patients getting first checkup, and the shortage of nurses and beds in the management of patients. This study demonstrate the application of hybrid method of Discrete Event Simulation (DES) and two types of Data Envelopment Analysis (DEA) specifically the Bi-Objective MCDEA BCC model and the Cross-Efficiency model to determine the most effective resource allocation in the inpatient department. The result of the simulation model has shown that the utilization of nurses per day exceeds 100% and the utilization of beds is relatively higher. Besides, the waiting times for patients to get their checkups are too long that exceeds 15 minutes in the inpatient department. The findings of the research show the number of nurses used in the inpatient department increased from 16 to 18, and the number of beds also increased from 36 to 38. The waiting time for patients to get their first checkup has been reduced to under 15 minutes. These additions and reductions can restore the problems faced by the inpatient department. Lastly, the optimum resource identified will enhance the quality of nurses, beds, and the flow of patients in the inpatient department to meet the Key Performance Indicators (KPI) of HUSM.